An innovative approach to strengthening health professionals' infection control and limiting hospital-acquired infection: video-reflexive ethnography. Issue 4 (23rd July 2015) - Iedema, Rick; Hor, Su-Yin; Wyer, Mary; Gilbert, Gwendolyn L; Jorm, Christine; Hooker, Claire; O'Sullivan, Matthew Vincent Neil
Abstract : Objective: To strengthen clinicians' infection control awareness and risk realisation by engaging them in scrutinising footage of their own infection control practices and enabling them to articulate challenges and design improvements. Design and participants: Clinicians and patients from selected wards of 2 hospitals in western Sydney. Main outcome measures: Evidence of risk realisation and new insights into infection control as articulated during video-reflexive feedback meetings. Results: Frontline clinicians identified previously unrecognised infection risks in their own practices and in their team's practices. They also formulated safer ways of dealing with, for example, charts and patient transfers. Conclusions: Video-reflexive ethnography enables frontline clinicians to identify infection risks and to design locally tailored solutions for existing risks and emerging ones.